Factors that influence the intention to use cryptocurrency among the public in Kuala Lumpur / Fatin Nursyakirah Halim - Halim, Fatin Nursyakirah (Faculty of Business and Management, 2019)
The purpose of this study was to determine the factors that influence the intention to use cryptocurrency among public in Kuala Lumpur. The independent variables consist of four factors including awareness, subjective norm, transaction processing and perceived behavioural control. Meanwhile the dependent variable of this study is intention to use cryptocurrency. A total of 79 usable questionnaires was keyed in and analysed by using SPSS software. Furthermore, this research has used purposive sampling to obtain accurate data from targeted respondents. All the data were collected for the purpose to create analysis of descriptive, reliability and regression analysis. In this study, findings show that there were three independent variables that have a significant and positive relationship towards intention to use cryptocurrency which are awareness, transaction processing and perceived behavioural control. From this study we can see, the finding is useful for body of knowledge, industry players and policy makers.